STRENGTHENING DEMOCRACY THORUGH POLITICAL EDUCATION IN INDONESIA - I Wayan Eka Santika; I Nengah Agus Tripayana (International Journal of Education and Social Science Studies, 2025)
This study explores the critical role of political education in strengthening democracy in Indonesia, a nation marked by vast cultural diversity and complex political dynamics. Despite significant institutional reforms since the 1998 reformation, challenges such as political polarization, limited civic engagement, and digital misinformation continue to undermine democratic consolidation. Through qualitative analysis based on in-depth interviews and document reviews, the research examines the current conceptualization and implementation of political education within formal schooling and non-formal settings. Findings reveal that political education in Indonesia often remains constrained by traditional, knowledge-based approaches, lacking emphasis on critical thinking, participatory learning, and digital literacy. Non-formal education and civil society initiatives show promise but face sustainability and integration challenges. The digital era presents both opportunities and risks, necessitating adaptive educational strategies that incorporate media literacy and ethical digital citizenship. This paper argues that to foster a resilient, substantive democracy, Indonesia must reform political education comprehensively—embracing innovative pedagogies, cross-sectoral collaboration, and continuous evaluation focused on civic engagement outcomes. Strengthening political education is not only a policy imperative but a fundamental civic responsibility to empower citizens in exercising their democratic rights and responsibilities.